Preterm Labor and the Associated Factors - Seno Adjie; Meily Meily; Ranti P Permatasari (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the risk factors that affect preterm labor in Dr. Cipto Mangunkusumo Hospital. Methods: This was an analytic descriptive study done in Emergency Unit of Dr. Cipto Mangunkusumo Hospital from July to December 2014. We recruited all women who gave birth in Emergency Unit of Dr. Cipto Mangunkusumo Hospital from July to December 2014 with gestational age less than 37 weeks. Of the total sampling method, we got 365 patients. We analyzed the data using chi square. Results: The characteristic age of subjects were 14.0% of less than 20 years old, 69.0% of 21-35 years old, and the rest were more than 35 years old. Most subjects (93.1%) were employed, 94.5% were married once, 62.3% of subjects had cesarean section history, 73.7% were primiparous, only 4.4% had history more than 1 abortion, and most of them were at 33-36 weeks of gestation. Socio-demographic factor associated with preterm labor and Preterm Premature Rupture of Membrane (PPROM) was age (p=0.011; OR 1.74; 95% CI 1.136-2.679). Obstetric history associated with preterm labor and PPROM was parity (p=0.017; OR 1.78; 95% CI 1.132-2.878). Conclusion: In this study, age and parity are associated with preterm labor and PPROM. [Indones J Obstet Gynecol 2017; 5-1: 3-7] Keywords: obstetric history, parity, PPROM, preterm labor, socio-demographic factors